Optimization of an Integrated Steel Retail Supply Chain Distribution in Multi-echelon Environment - Ramkrishna Punjaji Manatkar; Manoj Kumar Tiwari; Taufik Roni Sahroni (International Journal of Supply Chain Management, 2019)
This paper presents the integrated, multi-objective, multi-echelon, multi-product environment optimization model for steel retail distribution network. Model formulated covers retail supply chain processes applicable for steel products starting from production of different grades of material, its transfer to company warehouse, then to distributor warehouse cum service center and finally to retailer. The input parameters considered are the cost of opening new warehouse, order costs, administrative cost, inventory holding cost, transportation costs and desired service level for serving customers. In order to solve the problem a Territory Defined Evolutionary Algorithm (TDEA) is utilized. The paper discusses a realistic application of the validity of the model. The model developed supports organization and distributor in deciding the optimal location for minimizing inventory and transportation cost after taking into account desired service level requirements of retail customers. The framework presented further assist distributor in allocating the retailers to respective DC. Moreover, the model formulated benefits distributor and retailers in maintaining optimal regular and safety stock after taking into account variation in lead time and demand.